Home and clinical office pressure measurements in assessment of the prevalence and markers of arterial hypertension phenotypes in a cohort study - E. V. Platonova; A. D. Deev; V. M. Gorbunov; S. A. Shalnova (Кардиоваскулярная терапия и профилактика)
Aim. To study a combined use of home (HBPM) and office (OBP) blood pressure  measurements in assessment of prevalence and predictors of hypertensive phenotypes  in population of 55 years and older.Material and methods. From prospective cohort of Moscow population, a sample was randomly formed (n=1871, 64% response), representative of parameters of general health, educational level, time of residence in Moscow, and with an equal number of men and women. Data of HBPM (4 days: 2 morning/2 evening) and OBP (2 measurements) were studied in complex after comparing the reproducibility of the valid results in 974 subjects.  The prevalence  of hypertensive phenotypes  was assessed in subjects  without treatment.  The main risk factors and previous anamnesis were analyzed as potential predictors of belonging to the identified phenotype.Results. Preliminary results of 1120 patients are presented: mean age was 68,9±8 years, 43% of men; 44% with antihypertensive therapy. Themean   levels  of  HBPM and   OBP  were  137,0±18,5/79,5±9,3  and 141,0±23,9/  79,9±13,1 mmHg, respectively. The reproducibility of HBPM data was not inferior to OBP (SD for SBP/DBP =18,5/9,3  vs. 23,9/13,1 mmHg, respectively). Among 556 subjects  without treatment  (68,8±8 years; 47% — men; 42% — OBP ≥140/90  mmHg; 39% — abdominal obesity (AO); 17% — smoking; 8% — diabetes  mellitus (DM); 8% — history of myocardial infarction (MI) and 5% — history of stroke.  The both  methods  revealed  normal  level of  blood  pressure   in 42%  of patients, stable arterial hypertension — in 32%, white coat hypertension (WCH) — in 10%, masked  hypertension  (MH) — in 16%. DM and MI history increased  by more than 1,5 times the MH risk. History of stroke and AO absence were predictors of WCH.Conclusion. HBPM reclassified data of arterial hypertension prevalence in the population. Combined use of HBPM and OBP allow to establish every sixth person  with ambulatory hypertension,  who requires antihypertensive treatment.  Low “sensitivity”  of HBPM in present  case “mask” stable arterial hypertension  in every second  patient with WCH and history of stroke.Working group:   Alexandri A. L.,  Balanova Yu. A.,  Kapustina A. V., Konstantinov V. V.,   Kukushkin S. K.,  Lelchuk I. N.,  Muromtseva G. A., Timofeeva T. N., Khudyakov M. B.